10.1093/gao/9781884446054.013.7002292402 (Inactive DOIs, 2018)
Background X-linked genetic diseases affect males and females through different inheritance patterns influenced by sex, where differential methylation caused by X-chromosome inactivation can present with a range of asymptomatic, mild, and severe symptoms in females. Targeted long-read sequencing (LRS) through adaptive sampling (AS) shows robust performance in characterizing genomic composition and methylation status within the X chromosome, but it is not optimal for nonhigh-molecular-weight (non-HMW) DNA. Herein, we optimized a targeted LRS for non-HMW DNA and validated its diagnostic utility in families with X-linked genomic variants reported by routine methods. Methods Twenty families with X-linked genetic defects reported by previous chromosomal microarray analysis and/or low-pass genome sequencing were recruited and underwent optimized targeted LRS. Genomic variants were detected and classified along with haplotype analysis for assessing allele-specific methylation changes. Results The AS-based protocol was optimized for DNA fragmentation with size selection, library construction, and sequencing, and demonstrated a minimum 15-fold enrichment of targets against nontargets compared with the standard AS-based protocol showing 8.1-fold enrichment. In addition, our optimized LRS detected all of the X-linked variants reported previously and revealed additional findings in 7/20 families (35%). This led to variant reclassification in 3/20 cases (15%) achieved through breakpoint resolution for structural variants and determination of gene methylation status. Conclusions Our study demonstrated an AS-based protocol optimized for non-HMW DNAs that enabled the comprehensive characterization of genomic and methylation changes, highlighting its robust performance in the genomic evaluation of X-linked genetic defects with promising broader application to other disease states.